Not just for the birds: Spiders as natural enemies of spruce budworm (Choristoneura fumiferana, Clem.) - Joseph J Bowden; Berni van der Meer; Eric RD Moise; Rob C Johns; Martin Williams (Zenodo, 2022)
The eastern spruce budworm ( Choristoneura fumiferana , Clem.) is a native irruptive forest pest that defoliates spruce-fir forests throughout North America’s boreal zone. Past studies suggest that successful spruce budworm population control requires high natural mortality from a variety of sources, including predators, especially from parasitoids and birds. While well represented in many different ecosystems, the role of generalist predatory spiders in these boreal systems remains largely unstudied. To determine the identity and percentage of spiders that predate on spruce budworm, we hand collected spiders from balsam fir ( Abies balsamea ) in stands with relatively high spruce budworm densities from forests in insular Newfoundland and Labrador, Canada. Using a spruce budworm specific TaqMan real time PCR assay we successfully amplified spruce budworm DNA in 32% of collected spiders. After spider molecular barcoding we found the web-builders Grammonota angusta Dondale, Pityohyphantes (aff. subarcticus ), Dictyna brevitarsa Emerton, and Estrandia grandaeva (Keyserling) represented 58% of the spiders feeding on spruce budworm, and the wandering hunter Philodromus rufus vibrans Dondale represented 11.8%. Our molecular approach was an effective means with which to identify recently consumed prey and natural enemies in this boreal system.